2021
DOI: 10.1053/j.semtcvs.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

How Effective Is Neoadjuvant Therapy Followed by Surgery for Pathologic Single-Station N2 Non–Small Cell Lung Cancer?

Abstract: The optimal treatment strategy for pathologic single-station N2 (pN2a1) non-Àsmall cell lung cancer (NSCLC)-surgery first followed by adjuvant treatment (SF) or neoadjuvant therapy followed by surgery (NS)-remains unclear. We compared disease-free survival (DFS) and overall survival (OS) after NS versus SF for pN2a1 NSCLC. We retrospectively identified patients with pN2a1 NSCLC resected between 2000 and 2018. Patients in the SF group had cN0 disease and were treated with surgery before adjuvant chemotherapy; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
(32 reference statements)
1
4
0
Order By: Relevance
“…28,29 Moreover, lacking randomized data on this topic, retrospective studies found no survival benefit of neoadjuvant treatment compared with upfront surgery in patients with minimal N2. 30,31 We observed that most uN2 cases in our study were single-level intranodal metastases, also after immediate resection. One of the strengths of the MEDIASTrial was the employment of independent data and monitoring specialists as well as upfront publication of protocol and statistical analysis plan.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…28,29 Moreover, lacking randomized data on this topic, retrospective studies found no survival benefit of neoadjuvant treatment compared with upfront surgery in patients with minimal N2. 30,31 We observed that most uN2 cases in our study were single-level intranodal metastases, also after immediate resection. One of the strengths of the MEDIASTrial was the employment of independent data and monitoring specialists as well as upfront publication of protocol and statistical analysis plan.…”
Section: Discussionsupporting
confidence: 55%
“…The higher rate of mediastinal nodal spread among patients receiving more diagnostic tests was also demonstrated by Sanz-Santos, demonstrating a 19.5% higher N2-3 prevalence in studies performing confirmatory mediastinoscopy. 24 Although this meta-analysis showed large heterogeneity, the randomized ASTER trial found a 32) 48 (31) .7900…”
Section: Discussionmentioning
confidence: 89%
“…5YS in published series of patients with persistent N2 disease after neoadjuvant therapy is poor compared with patients with pN0 disease (5YS <20 vs. 30-40%, respectively). 3,15,[22][23][24][25] In our study, the risk factors affecting recurrence were to have a nonsquamous cell histological tumor (p ¼ 0.006) and to receive chemotherapy only (p ¼ 0.04). Similarly, in the study of Montemuiño et al, locoregional recurrence was significantly lower in the CRT group (8.5 vs. 13.5%; p ¼ 0.047), but distant recurrence rates were similar in the two groups.…”
Section: Discussionmentioning
confidence: 59%
“…5YS in published series of patients with persistent N2 disease after neoadjuvant therapy is poor compared with patients with pN0 disease (5YS <20 vs. 30–40%, respectively). 3 15 22 23 24 25…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, comparing survival in cN2 and pN2 cases, no difference in survival was observed between the two groups. 15,16 However, the point to be noted here is that most of the cases here are T1-T2 cases. Regardless of the T factor, OS is reported to be between 25% and 27% in patients who were operated on as cN0 but were found to have pN2 in different series, and this rate rises to 35-50% with the addition of adjuvant therapy.…”
Section: Discussionmentioning
confidence: 83%